Green banking practices and HRM in enchancing innovation capability: A knowledge management perspective on sharia banking performance - Satria Avianda Nurcahyo; Tri Wikaningrum; Anis Malik Thoha (Diponegoro International Journal of Business, 2025)
This study investigates the influence of green banking practices and human resource management (HRM) on innovation capability and examines the mediating role of knowledge management in enhancing Sharia banking performance. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), data were collected through questionnaires distributed to employees using a saturated sampling technique. The findings reveal that HRM significantly affects green banking, innovation capability, and knowledge management. However, innovation capability does not significantly mediate the relationship between green banking and performance, nor between HRM and performance. In contrast, knowledge management significantly mediates the effect of HRM on Sharia banking performance. The results highlight the critical role of HRM and knowledge management in driving organizational performance, while emphasizing the need for more effective implementation of green banking and innovation strategies to realize their full potential impact.